2020
DOI: 10.21037/atm-20-7831
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics and metabolomics of raw rhubarb and wine-processed rhubarb in the treatment of rats with intracerebral hemorrhage

Abstract: Background: To explore the mechanisms of raw rhubarb and wine-processed rhubarb treatment in a rat model of intracerebral hemorrhage (ICH).Methods: After adapting to their environment, 30 male Wistar rats were divided into 5 treatment groups: blank control group (CK) (normal saline), sham operation group (SICH) (normal saline), ICH model group (ICH) (normal saline), ICH + raw rhubarb enema group (RO) (raw rhubarb 3.60 g/kg), and ICH + wineprocessed rhubarb enema group (WRO) (wine-processed rhubarb 3.60 g/kg). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Chae et al showed that CHR alleviated hippocampal neuronal cell death via inhibition of Drp1-dependent mitochondrial fission [60]. In addition, our previous studies proved that rhubarb treatments effectively protected nerve cell damage by increasing of the antioxidative stress and anti-inflammatory responses in rat with ICH [61], and studies have shown that CHR is the most abundant- free anthraquinone component in the rhubarb [12]. Therefore, we hypothesized that CHR extracted from rhubarb has a protective effect on ICH following brain injury.…”
Section: Discussionmentioning
confidence: 79%
“…Chae et al showed that CHR alleviated hippocampal neuronal cell death via inhibition of Drp1-dependent mitochondrial fission [60]. In addition, our previous studies proved that rhubarb treatments effectively protected nerve cell damage by increasing of the antioxidative stress and anti-inflammatory responses in rat with ICH [61], and studies have shown that CHR is the most abundant- free anthraquinone component in the rhubarb [12]. Therefore, we hypothesized that CHR extracted from rhubarb has a protective effect on ICH following brain injury.…”
Section: Discussionmentioning
confidence: 79%
“…In animal models, subarachnoid hemorrhage (SAH) is quite hard to simulate so that it could correspond to the SAH occurring in humans. The main cause of SAH in humans is the rupture of an aneurysm, while the rodent models of SAH are defined as non-aneurysmal ( 22 ). In an attempt to do so, several techniques are performed, such as injection of blood into the subarachnoid space/cerebral ventricles or by endovascular perforation of a subarachnoid vessel.…”
Section: Stroke Metabolomicsmentioning
confidence: 99%
“…It is believed that an adequate method that models the pathophysiology in humans most closely is the intraluminal Circle of Willis perforation injury at the internal carotid artery bifurcation ( 23 ). Nonetheless, other models such as blood (homologous or heterologous) injection into pre-chiasmatic cistern ( Figure 2C ) and cisterna magna ( Figure 2D ) compromising anterior and posterior blood supply, respectively, are frequently used ( 22 ). Apart from the standard physiological parameters affected by SAH, which could be tracked in animal experiments (e.g., blood pressure, oxygen tension, cerebral perfusion pressure, etc.…”
Section: Stroke Metabolomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the lowered purgative effect, the application of prepared rhubarb became much safer than raw rhubarb. So, prepared rhubarb was recorded in the list of “Functional Food Raw Materials” of China and could be given to children and old people for the treatment of diseases related to abnormal hemorheology in clinics ( Wang et al, 2003 ; Wang et al, 2020 ; Zhao, 2020 ).…”
Section: Introductionmentioning
confidence: 99%